Theoretical description of functionality, applications, and limitations of SO2 cameras for the remote sensing of volcanic plumes - Kern, Christoph; Kick, Felix; Lübcke, Peter; Vogel, Leif; Wöhrbach, Markus; Platt, Ulrich (Atmospheric measurement techniques, 2010)
This study gives a theoretical basis for the pertinent aspects of working with SO2 camera systems, including the measurement principle, instrument design, data evaluation and technical applicability.